2014
DOI: 10.1111/nyas.12388
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting impulsivity and its relationships to drug addictions

Abstract: Addictions are often characterized as forms of impulsive behavior. That said, it is often noted that impulsivity is a multidimensional construct, spanning several psychological domains. This review describes the relationship between varieties of impulsivity and addiction-related behaviors, the nature of the causal relationship between the two and the underlying neurobiological mechanisms that promote impulsive behaviors. We conclude that the available data strongly supports the notion that impulsivity is both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
210
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(236 citation statements)
references
References 271 publications
(371 reference statements)
9
210
1
2
Order By: Relevance
“…The current findings also support the contention that impulsivity should be conceptualised as a multifaceted construct (Jentsch et al, 2014;Patton et al, 1995;Stanford et al, 2009). Specifically, it was found that the sub-traits of impulsivity differed in their capacity to account for varying alcohol consumption behaviours.…”
Section: Discussionsupporting
confidence: 74%
“…The current findings also support the contention that impulsivity should be conceptualised as a multifaceted construct (Jentsch et al, 2014;Patton et al, 1995;Stanford et al, 2009). Specifically, it was found that the sub-traits of impulsivity differed in their capacity to account for varying alcohol consumption behaviours.…”
Section: Discussionsupporting
confidence: 74%
“…For example, D 2 -like receptor availability is influenced by receptor density, levels of endogenous ligand that compete for the same binding site as the radiotracer, or heterogeneity in pools of synaptic, extrasynaptic, and intracellular receptors that likely have different functional implications for neurotransmission (Guo et al, 2010;Ito et al, 2011). Therefore, the multiple potential influences on receptor availability have limited the interpretation of PET-based measures to clarify molecular abnormalities that occur in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this goal, we conducted in vitro and in vivo assessments of dopamine receptors within the same vervet monkeys and compared these measures to the behavioral performance of the same subjects in the reversal-learning task that, in part, measures inhibitory control (Izquierdo and Jentsch, 2012). We found that individual differences in striatal D 2 -like, but not D 1 -like, receptor availability measured with PET related to the function of D 2 -like receptors, determined by measuring spontaneous and dopamine agonist-induced eyeblink rate (EBR; Lowry et al, 1951), and D 2 -like receptor density assessed in postmortem homogenates.…”
Section: Introductionmentioning
confidence: 99%
“…for review Grant, Potenza, Weinstein, & Gorelick, 2010;Lubman, Yücel & Pantelis, 2004;Volkow, Fowler & Wang, 2003). A core set of frontostriatal circuits was found in various types of impulsivity, substance addiction (Jentsch et al, 2014), and pathological gambling (elGuebaly, Mudry, Zohar, Tavares, & Potenza, 2011). Jentsch et al (2014) have shown a strong relationship between impulsivity and addiction-related behaviours, and also the potential susceptibility of those with poor impulse control for substance or behavioural addiction.…”
Section: Introductionmentioning
confidence: 99%
“…A core set of frontostriatal circuits was found in various types of impulsivity, substance addiction (Jentsch et al, 2014), and pathological gambling (elGuebaly, Mudry, Zohar, Tavares, & Potenza, 2011). Jentsch et al (2014) have shown a strong relationship between impulsivity and addiction-related behaviours, and also the potential susceptibility of those with poor impulse control for substance or behavioural addiction. Indeed, impulsivity was associated with both substanceand non-substance addictions in some studies (Maccallum, Blaszczynski, Ladouceur, & Nower, 2007;VerdejoGarcía, Lawrence, & Clark, 2008).…”
Section: Introductionmentioning
confidence: 99%